2013
DOI: 10.1021/jp407562t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8-Oxoguanine on DNA Structure and Deformability

Abstract: 8-Oxoguanine (oxoG) is an abundant product of oxidative DNA damage. It is removed by repair glycosylases, but exactly how the enzymes recognize oxoG in the large surplus of undamaged bases is not fully understood. The lesion may induce changes in the properties of naked DNA that facilitate the recognition. In this work, we assess the effect of oxoG on DNA structure and mechanical deformability. We performed extensive unrestrained, atomic resolution molecular dynamics simulations to parametrize a nonlocal, rigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…In previous simulations we found that the presence of 8oxoG in DNA can result in local alterations of the backbone and sugar pucker fine structure (13,14). However, no significant differences in the helical deformability including twist deformability were observed (14). This is supported by experimental crystal structures of 8oxoG containing DNA that also indicate distinct changes in the nucleo-backbone structure compared to undamaged DNA.…”
Section: Discussionmentioning
confidence: 91%
“…In previous simulations we found that the presence of 8oxoG in DNA can result in local alterations of the backbone and sugar pucker fine structure (13,14). However, no significant differences in the helical deformability including twist deformability were observed (14). This is supported by experimental crystal structures of 8oxoG containing DNA that also indicate distinct changes in the nucleo-backbone structure compared to undamaged DNA.…”
Section: Discussionmentioning
confidence: 91%
“…T 19 UMe 98 1 1 0 HMe 97 1 2 0 FMe 95 3 2 0 T 7 C 8 /G 17 A 18 UMe 68 20 9 3 HMe 56 31 8 5 FMe 63 25 6 6 42°for HMe, 40°for FMe). A correlation between twist and mixed state populations has been observed in other sequences before [20,31,55]. HMe had the highest value of twist and the highest population of mixed BI/BII states (39%) at the T 7 C 8 /G 17 A 18 step.…”
Section: Resultsmentioning
confidence: 52%
“…The trajectories are used to extract the variances and covariances of all intra‐ and interhelical parameters associated with the sampled DNA conformations resulting in a stiffness matrix to describe the deformability of the duplex in terms of effective force constants for helical deformations. Details of the approach have been described in previous publications . The overall stiffness is characterized by conformational entropy per rigid base coordinate, as described earlier …”
Section: Methodsmentioning
confidence: 99%